2018
DOI: 10.18517/ijaseit.8.5.5006
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Dengue Disease Using Extreme Learning Machine

Abstract: Dengue disease is one of the serious and dangerous diseases that cause many mortality and spread in most area in Indonesia. There are about 201,885 cases had been reported in 2016 including 1,585 death cases. The availability of nowadays clinical data of Dengue disease can be used to train machine learning algorithm in order to automaticaly detect the present of Dengue disease of the patients. This study will use the Extreme Learning Machine (ELM) method to classify the dengue by using the clinical data so tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Gowthaman compares SVM with ELM. From several experiments, it is concluded that ELM is better than SVM in terms of results and learning speed [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gowthaman compares SVM with ELM. From several experiments, it is concluded that ELM is better than SVM in terms of results and learning speed [15].…”
Section: Introductionmentioning
confidence: 99%
“…Nemissi uses ELM for the classification of breast cancer with excellent results. Besides, ELM has also been used to solve problems such as forecasting the inflation rate in Indonesia [14], the detection of dengue fever [15], the diagnosis of breast cancer [16], and others showing results with an average accuracy rate above 90%. Gowthaman compares SVM with ELM.…”
Section: Introductionmentioning
confidence: 99%
“…The medical use of image textures has been reported in the previous studies. Examples are early detection of Alzheimer's disease [ 6 ], dengue fever [ 7 ], osteoarthritis [ 8 , 9 ], and lung cancer [ 10 , 11 ], while research on disease diagnosis based on iris image feature extraction is used to diagnose kidney disease [ 12 ] and heart disease [ 13 ], detect Alzheimer's [ 14 ], detect stomach disorders [ 15 ], and others.…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques have been carried out on medically related datasets for many purposes. Due to the broad scope of the medical and health fields, various research topics are found which ranges from diagnosis [3]- [5], diseases [3], [4], [6]- [11], patient's condition [12]- [17], prescription and medication [1], [18]- [21], to genomics [22]- [24].…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia, compared to a very large population and a very large area of the country, the studies regarding the medical records or electronical health are very limited. Some of the studies which focus on the local context are published in [11] and [15]. The first article presents the study results of early dengue disease detection with the dataset captured from some public health (PUSKESMAS).…”
Section: Introductionmentioning
confidence: 99%